2005
DOI: 10.1111/j.1365-2109.2004.01180.x
|View full text |Cite
|
Sign up to set email alerts
|

Stress-related physiological responses to handling in common dentex (Dentex dentex Linnaeus, 1758)

Abstract: The e¡ects of handling on haematocrit, haemoglobin, plasma glucose, lactate and total amino acids, liver glycogen and hepatic activity of fructose 1,6-bisphosphatase (FBPase) and alanine aminotransferase (AAT) were investigated in common dentex (Dentex dentex Linnaeus,1758). A total of 42 ¢sh (50-g weight) were subjected to handling (netting and shaking in the air for 45 s). Six ¢sh were sampled at 0, 0.5, 1, 2, 4, 8 and 12 h after handling. Six unstressed ¢sh were also sacri¢ced at each time and used as contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
25
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 43 publications
7
25
1
8
Order By: Relevance
“…The present data support the studies where it is clear that these haematological indicators of secondary stress response are mainly displayed in chronic stress situations [24]. It has been shown that high stocking density, considered as an aquaculture-related chronic stressor [43] produce on juveniles of gilthead seabream, haemoconcentration, as a strategy for increasing oxygen carrying capacity of blood during periods of high energy demand [51][52][53].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The present data support the studies where it is clear that these haematological indicators of secondary stress response are mainly displayed in chronic stress situations [24]. It has been shown that high stocking density, considered as an aquaculture-related chronic stressor [43] produce on juveniles of gilthead seabream, haemoconcentration, as a strategy for increasing oxygen carrying capacity of blood during periods of high energy demand [51][52][53].…”
Section: Discussionsupporting
confidence: 74%
“…Most research on the acute stress has been focused on handling [6,19,23,24] and capture [25][26][27][28] but no information is available on physiological effects of vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…the chasing and swimming of fish, physical injury provoked by the contact among fish and with the net and anoxia by air exposure (Mugnier et al, 1998;Arends et al, 1999;Ross and Ross, 1999;Barcellos et al, 2001;Morales et al, 2005). Confirming the literature regarding fish stress, elevated circulating cortisol and glucose of pacu were short-term responses in both air-exposed fish after capture and the recovery occurred within 24 hours.…”
Section: Discussionsupporting
confidence: 69%
“…Various stressors, including fish capture (Mugnier et al, 1998;Arends et al, 1999;Barcellos et al, 2001;Rocha et al, 2004;Morales et al, 2005), are necessary components of modern intensive aquaculture (Wendelaar Bonga, 1997). The fish response to such stressors involves a series of physiological changes in an attempt to compensate for the challenge imposed upon it and, thereby cope with the stress.…”
Section: Introductionmentioning
confidence: 99%
“…O mesmo resultado foi obtido com os peixes-controle. De acordo com Morales et al (2005), mudanças nas respostas hematológicas de estresse, como o hematócrito, normalmente não são observadas em exposições agudas, sendo mais responsivo em exposições crônicas. Figura 3.…”
Section: Resultsunclassified